On the biogeography of earthworms of the primitive genus Drawida Michaelsen, 1900 (Clitellata: Moniligastridae) in the Indian subcontinent - Narayanan, S. Prasanth; Kumari, Shailja; Kurien, Vijo T.; Thomas, A.p.; Paliwal, R.; Julka, J.m. (Zootaxa, 2025)
Among the various Indian earthworm genera, the moniligastrid earthworm genus Drawida is the most species rich and has undergone extensive species radiation in Peninsular India. It is believed that Drawida entered Peninsular Indian landmass after the suturing of Indian plate with Laurasia during the Tertiary period in the Cenozoic Era. There are a number of hypotheses about the occurrence of various wet zone species in Peninsular India and its disjunct distribution in peninsula, northeast India and Sri Lanka. Here in this work, based on the thorough analysis of various available literatures on the various knowledge domains, we are further discussing the biogeography of Drawida in the Indian subcontinent in detail. We postulate that the Drawida species entered the Indian peninsula through the north-eastern corner of present-day India, during the middle Miocene epoch (during Burdigalian age: ca. 16 Ma) and taken the Eastern Ghats-east coast route to colonise the Western Ghats mountain ranges and undergone rapid diversification. Sri Lanka holds lone two endemic Drawida species/subspecies, and it is assumed that Drawida could not colonize Sri Lanka as it separated from the mainland India in the Miocene and only connected with mainland during several Pleistocene periods of low sea level. Hence the species occurring in Sri Lanka would have been carried there from the mainland India. Populations of Drawida species from Western Ghats, Eastern Ghats, north-eastern hills of India and Sri Lanka need to be sampled and studied in detail making use of the modern molecular techniques, which can solve many problems in the phylogeny and their biogeographical relationships.